Development of international entrepreneurship based on corporate accounting and reporting according to IFRS : part B - Eshov, Mansur P.; Abdurakhmanova, Gulnora K.; Burkhanov, Aktam U.; Abdusalomova, Nodira B.; Ergasheva, Shakhlo T. (Emerald Publishing Limited, 2024)
Development of International Entrepreneurship based on Corporate Accounting and Reporting According to IFRS: Part B offers a thorough exploration of applying International Financial Reporting Standards (IFRS) in contemporary international entrepreneurship management, emphasizing practical issues. Introducing an innovative perspective on international entrepreneurship management through IFRS-based corporate accounting and reporting, this volume features comprehensive analysis of developing countries' experiences in mutual trade integration using IFRS, exemplified by the EAEU and BRICS bloc. Development of International Entrepreneurship based on Corporate Accounting and Reporting According to IFRS: Part B presents detailed discussions on digital modernization within IFRS, in turn examining industry-specific aspects of international entrepreneurship development and international trade cooperation experiences. Targeting scholars interested in IFRS and international entrepreneurship, Part B provides insights into practical experiences with IFRS application in corporate accounting and reporting. It adds to ongoing discussions on international trade development through IFRS modernization and application.
Keywords: Corporations -- Accounting.; Entrepreneurship -- Management.; Entrepreneurship -- Technological innovations.; Business & Economics -- Accounting -- General.; Accounting.; elektronické knihy; electronic books